RESEARCH OF PHYSICO-CHEMICAL PROPERTIES OF “JAMU” POWDER FROM MORINGA LEAF, BELUNTAS LEAF, AND NONI LEAF EXTRACTS - Angelica Apnia Priyambodo; Dedin Finatsiyatull Rosida (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Jamu has been used by Indonesian people for generations. Noni, Moringa, and Beluntas leaves have the potential to be utilized as herbal medicine because they contain natural antioxidants such as alkaloids, anthraquinones, tannins, flavanoids. ascorbic acid, and phenolics. Maltodextrin and gum arabic are fillers commonly used in the manufacture of powdered beverages. Gum arabic has a great emulsifying property, but it is relatively expensive. Meanwhile, maltodextrin is a good encapsulant, but its properties as an emulsifier are not good. The purpose of this research was to determine the effect herbal leaf sources (moringa, noni, beluntas) as well as the proportion of maltodextrin and gum arabic on the physical and chemical properties of herbal powder drinks. This research used a 2 Factorial Completely Randomized Design (CRD) with 2 (two) replicates. The results obtained in herbal powder drinks have a moisture content of 3.05-4.05%, ash content of 0.35-1.24%, vitamin C content of 39.45-210.59 mg/100g, solubility of 78.94- 82.91%.